Access to health care services among pregnant women in rural communities: In-depth case studies from Bagamoyo district in Tanzania - Barongo, Vivien Kokutangilila (Curtin University, 2015)
Tanzania National Health Policy declares free health services for pregnant women. However, rural women still face barriers accessing the services. A naturalistic ethnographic approach focuses on stories and experiences of women, spouses and healthcare personnel, supporting examination of constraining and enabling factors of health service provision in Bagamoyo District. Outcomes inform existing knowledge in scholarly and applied fields; promote culturally-sensitive empirical research on access to healthcare; and assist in improving healthcare services accessibility and utilisation.